2023
DOI: 10.2337/db22-0680
|View full text |Cite
|
Sign up to set email alerts
|

Metrnl Alleviates Lipid Accumulation by Modulating Mitochondrial Homeostasis in Diabetic Nephropathy

Abstract: Ectopic lipid accumulation in renal tubules is closely related to the pathogenesis of diabetic kidney disease (DKD) and mitochondrial dysfunction is thought to play a key role in lipid accumulation. Therefore, maintaining mitochondrial homeostasis holds considerable promise as therapeutic strategies for the treatment of DKD. Here we reported that Meteorin-like (Metrnl) gene product mediates lipid accumulation in the kidney and has therapeutic potential for DKD. We confirmed the reduced expression of Metrnl in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“… 35 Considering the association of atherosclerosis and blood pressure, 36 the inverse correlation between Metrnl and blood pressure can be well explained. Zhou et al 37 reported that recombinant Metrnl administration or Metrnl-specific overexpression in the kidney relieves renal injuries in diabetic mice. Here we show serum Metrnl is inversely related to Creatinine, in line with previous result.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Considering the association of atherosclerosis and blood pressure, 36 the inverse correlation between Metrnl and blood pressure can be well explained. Zhou et al 37 reported that recombinant Metrnl administration or Metrnl-specific overexpression in the kidney relieves renal injuries in diabetic mice. Here we show serum Metrnl is inversely related to Creatinine, in line with previous result.…”
Section: Discussionmentioning
confidence: 99%
“…Metrnl is a recently discovered hormone produced by skeletal muscles and adipose tissue in response to exercise and cold exposure. Metrnl-specific overexpression or recombinant Metrnl administration in the kidney regulates renal tubular lipid metabolism through mitochondrial homeostasis mediated by the Sirtuin 3(Sirt3)-AMPK/uncoupling protein 1(UCP1) signaling axis, alleviates renal injury, and delays DKD in diabetic mice ( 193 ).…”
Section: Targeting Lipid Metabolism For Dkd Treatmentmentioning
confidence: 99%
“… 144 SIRT3 deacetylates mitochondrial uncoupling protein 1 (UCP1), promoting the dissipation of proton gradient across the inner mitochondrial membrane, which leads to the generation of heat instead of ATP. 145 , 146 Additionally, ROS can induce post-translational modifications to promote the activation of UCPs and subsequently trigger mitochondrial uncoupling. 147 Moreover, SIRT3 contributes to glutathione production by activating isocitrate dehydrogenase (IDH2), which catalyzes the oxidation of isocitrate to generate α-ketoglutarate and produce NAD(P)H. 148 Further, NADPH is crucial in reducing GSSG to GSH 149 and serves as an electronic transmitter for NOS or NOXs to generate NO or O 2 ·- /H 2 O 2 .…”
Section: Redox Modulations By Nad + -Dependent Sir...mentioning
confidence: 99%